Mixed Reality for Remote Supervision and Risk Assessment of Unstable Terrains - Rocha, Lidia; Futai, Marcos M.; Vivaldini, Kelen C. T. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais Estendidos do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Operating drones in unstable terrains poses safety and logistical challenges. This Serious Game leverages Mixed Reality (MR) to simulate hazardous environments using Virtual Reality (VR) for training and Augmented Reality (AR) for collaborative analysis. Objective: This work develops an MR-based training simulation where players explore unstable environments, evaluate pre-planned drone trajectories, and predict terrain changes to improve flight strategy and risk assessment. Methodology: Players use VR to safely explore hazardous terrains, analyze drone data, and rehearse flight paths before real missions. The system gradually trains operators to transition to real drone use. A future AI prediction module is intended to enhance terrain analysis by anticipating environmental changes. AR supports strategic collaboration by enabling shared visualization and discussion of unstable environments. Expected Results: The game aims to enhance spatial awareness, improve flight planning, and support safer decision-making. It offers a risk-free environment to evaluate terrain evolution and drone strategies without field exposure.